2010
DOI: 10.5688/aj7409166
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Malaysian Pharmacy Students' Career Preferences

Abstract: Objectives. To identify and evaluate factors affecting the career preferences of fourth-year bachelor of pharmacy (BPharm) students in Malaysia in the presence of a 4-year period of mandatory government service. Methods. A validated self-administered questionnaire was used in this cross-sectional study to collect data from final-year BPharm students enrolled at 3 government-funded universities and 1 private university in Malaysia. Both descriptive and inferential statistics were used for data analysis. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
63
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 7 publications
11
63
3
2
Order By: Relevance
“…17 In contrast, a Malaysian report by Hasan and colleagues indicated that the top 3 factors impacting finalyear pharmacy students in selecting career destination were salary, benefits, and geographical location. 18 The higher percentage of male students compared to female students who wanted to travel abroad was associated with a significant difference in the order by which male and female students rated the influence of having the desire and/or opportunity to travel abroad on their postgraduation intentions. This may reflect male students having a more adventurous spirit compared with female students.…”
Section: Discussionmentioning
confidence: 99%
“…17 In contrast, a Malaysian report by Hasan and colleagues indicated that the top 3 factors impacting finalyear pharmacy students in selecting career destination were salary, benefits, and geographical location. 18 The higher percentage of male students compared to female students who wanted to travel abroad was associated with a significant difference in the order by which male and female students rated the influence of having the desire and/or opportunity to travel abroad on their postgraduation intentions. This may reflect male students having a more adventurous spirit compared with female students.…”
Section: Discussionmentioning
confidence: 99%
“…[16] In a Malaysian study, hospital pharmacy and community pharmacy were the preferred options among students. [10] Although many students were unaware about post-graduate prospects of pharmacy education, still substantial numbers of students were interested in research while some were unsure about their decision. It has been reported that relatively few pharmacy graduates pursue research-related post-graduate paths.…”
Section: Discussionmentioning
confidence: 99%
“…Geographical location, salary, and benefits were the most important factors in selecting a career destination. [10] In Pakistan, little is known about pharmacy students' attitude and preferences. Therefore, this study was designed to identify fourth year Doctor of Pharmacy (Pharm.D) students' attitude towards pharmacy profession, their career preferences, and factors involved in this selection.…”
Section: Introductionmentioning
confidence: 99%
“…[8] A Malaysian study found that most of the pharmacy students were interested in hospital pharmacy and community pharmacy. [9] Our previous study conducted in fourth year pharmacy students showed that the preferred career areas were clinical pharmacy, industrial pharmacy, and hospital pharmacy. [10] Through literature review, it has been identified that no particular study yet has been published regarding the attitude and career preferences of first year Doctor of Pharmacy (PharmD) students in Pakistan.…”
Section: Introductionmentioning
confidence: 99%